Parent perception on active music experience : family-centered music therapy & children with autism spectrum disorder - Onitsuka, Aiko (2018)
I describe the parents' perception of active music experience with their child who has Autism Spectrum Disorder, and the role active music experience plays on the level of parenting stress. The Parenting Stress Index Japanese Edition was conducted pre- and post music therapy phase to see the difference in the parenting stress between this period. A semi-structured interview was conducted to better understand parents' stress behind the child's characteristics and the parent's characteristics, and to further explore their active music therapy experience to make conclusions about the family practice. I completed data collection and Music Therapy Intervention with a total of four families in Japan. Family A includes a father, a mother and an 8 year old boy with Autism Spectrum Disorder; family B includes a father, a mother and a 4 year old boy with Autism Spectrum Disorder; family C includes a mother and an 11 year old boy with Autism Spectrum Disorder; and family D includes a mother and an 8 year old boy with Autism Spectrum Disorder (PDD-NOS). The findings revealed that the use of active music experience decreased the stress level of parents whose children had Autism Spectrum Disorder. Parents perception on parenting stress, however, in terms of what areas parents' perceived stress and how they identified stress varied. The findings of this study gives insight into the uniqueness of each parent's cause of stress, the parents' trauma, and the significant musical moment that triggers parents to change their way of perceiving their parenting stress. Recognizing parenting stress as a negative factor impacting family dynamics and offering support may better guide music therapists in the family practice to meet the needs of parents and children with Autism Spectrum Disorder.